Expression of antigen-presenting cells in lung of postmortem SARS-CoV-2 cases: Antigen-presenting cells in SARS-CoV-2 - Rasheed, Taban Kamal (Cellular and Molecular Biology, 2024)
Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2) is a deadly pulmonary disease with impaired immunological response that causes significant tissue damage and organ failure. Postmortem examination of the lung is a useful tool for understanding the immunopathogenesis of this virus. Lung autopsy samples from seven dead SARS-CoV-2 patients were obtained and evaluated using hematoxylin and eosin stain to analyze the histopathological changes in those samples, on the other hand, Immunohistochemical (IHC) staining was used for detection of CD21, CD1a, CR1 (CD35), CD68, Myeloperoxidase (MPO), CD15, CD56, CD3, CD20, CD4, and CD8 cells markers. Histopathological examination revealed diffuse alveolar damage with extensive parenchymal architecture distortion, intravascular fibrin clot, deposition of collagen fibers, vascular congestions and blood vessels containing thrombi, pneumocyte type II with inflammatory cell infiltration. The IHC staining for the innate immune cells such as antigen-presenting cells (APCs) including dendritic cells, Macrophages, and neutrophils showed a strong positive staining, while CD56 Natural killer (NK) cells showed negative staining. On the other hand, the specific immune cells including; CD20 B cells, CD3 T cells, and CD4 helper T cells, showed positive staining while CD8 Cytotoxic T cells showed negative staining. The lung autopsy samples from patients with COVID-19 confirmed the presence of APCs through the positive staining of CD21, CD1a, CD35, CD68, MPO, and CD15 expressed the virus recognition, proinflammatory cytokine production, and adaptive immune cells activation through CD3, CD4, and CD20 positive staining and the role of APCs in the severity of pulmonary infection and pathogenesis of SARS-CoV-2 infection however the absence of the CD56 NK and CD8 cytotoxic T explains the worse infection status for the patients.